596 Multidisciplinary in-depth investigation in a young athlete suffering from syncope caused by myocardial bridge. (8th December 2021) - Brancaccio, Mariarita; Cesaro, Arturo; Monda, Emanuele; D'Argenio, Valeria; Casaburi, Giorgio; Mazzaccara, Cristina; Limongelli, Giuseppe; Calabro, Paolo; Lombardo, Barbara; Scudiero, Olga; Frisso, Giulia
Abstract: Aims: Laboratory medicine along with genetic investigations are taking on an increasingly important role in monitoring athlete's health conditions. Acute or intense exercise can lead to metabolic imbalances, muscle injuries, or can point up cardiovascular disorders. Methods and results: This study aimed to monitor the health status of a basketball player, through an integrated approach including biochemical and genetic investigations and advanced imaging techniques, to shed light on the causes of recurrent syncope he experienced during exercise. Biochemical analyses showed that the athlete had abnormal iron, ferritin, and bilirubin levels. Coronary computed tomographic angiography highlighted the presence of an intramyocardial bridge, suggesting this may be the cause of the observed syncopes. The athlete was excluded from competitive activity. To understand if this cardiac malformation could be caused by an inherited genetic condition, both array-CGH and whole exome sequencing were performed. Array-CGH showed two intronic deletions involving MACROD2 and COMMD10 genes, which could be related to the congenital heart defect; the whole exome sequencing highlighted the genotype compatible with the Gilbert syndrome. However, no clear pathogenic mutations related to the patient's cardiological phenotype were detected, even after applying machine learning methods. Conclusions: This case highlights the importance and the need to provide exhaustive personalized diagnostic work-up for the athletes to cover the cause of their malaise, safeguarding their health. This multidisciplinary approach can be useful to create ad personam training and treatments, thus avoiding the appearance of diseases and injuries which, if underestimated, can become irreversible disorders and sometimes can lead to the death of the athlete.